Characterization of the Zebrafish Glycine Receptor Family Reveals Insights Into Glycine Receptor Structure Function and Stoichiometry - Low, Sean Eric; Ito, Daishi; Hirata, Hiromi (Frontiers in Molecular Neuroscience, 2018)
To study characterization of zebrafish glycine receptors (zGlyRs), we assessed expression and function of five α- and two ß-subunit encoding GlyR in zebrafish. Our qPCR analysis revealed variable expression during development, while in situ hybridizations uncovered expression in the hindbrain and spinal cord; a finding consistent with the reported expression of GlyR subunits in these tissues from other organisms. Electrophysiological recordings using Xenopus oocytes revealed that all five α subunits form homomeric receptors activated by glycine, and inhibited by strychnine and picrotoxin. In contrast, ß subunits only formed functional heteromeric receptors when co-expressed with α subunits. Curiously, the second transmembranes of both ß subunits were found to lack a phenylalanine at the sixth position that is commonly associated with conferring picrotoxin resistance to heteromeric receptors. Consistent with the absence of phenylalanines at the sixth position, heteromeric zGlyRs often lacked significant picrotoxin resistance. Subsequent efforts revealed that resistance to picrotoxin in both zebrafish and human heteromeric GlyRs involves known residues within transmembrane 2, as well as previously unknown residues within transmembrane 3. We also found that a dominant mutation in human GlyRα1 that gives rise to hyperekplexia, and recessive mutations in zebrafish GlyRßb that underlie the bandoneon family of motor mutants, result in reduced receptor function. Lastly, through the use of a concatenated construct we demonstrate that zebrafish heteromeric receptors assemble with a stoichiometry of 3α:2ß. Collectively, our findings have furthered our knowledge regarding the assembly of heteromeric receptors, and the molecular basis of ß subunit-conferred picrotoxin resistance. These results should aid in future investigations of glycinergic signaling in zebrafish and mammals.